Informal Institutions and Global Trade: Real Effects of the Elusive - Eiji Fujii (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
Countries routinely participate in intergovernmental forums such as the G7, G20, BRICS, and MIKTA. These informal institutions—unlike formal bodies such as the EU and WTO—lack permanent administrative structures, operate through rotating presidencies, and do not issue legally binding commitments. Although often overlooked as drivers of global trade, their formation and evolution embody underlying structural shifts in the world economy. Using data for over 200 countries spanning 1994-2023, this study introduces informal institutions as a distinct determinant of trade within the gravity framework. We find that BRICS exerts trade-facilitating effects comparable to those of formal agreements such as regional trade agreements and WTO accession. This highlights a novel channel of international integration beyond legal commitments.
Keywords: F10; F13; F14; O19; 330; informal institutions; international trade; gravity model; BRICS; MIKTA; G20; G7